A Note on the Rotationally Symmetric SO(4) Euler Rigid Body - Falqui, G. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
We consider an SO(4) Euler rigid body with two 'inertia momenta' coinciding. We study it from the point of view of bihamiltonian geometry. We show how to algebraically integrate it by means of the method of separation of variables.